Flame-retardant polyurethane composite material and preparation process thereof

By introducing phosphorus-modified cyclotetrasiloxane and modified lignin microspheres into the polyurethane material, and combining dioxime monomers and N,N-dimethylhexylamine and other components, a polyurethane composite material with excellent flame retardant properties was prepared, which solved the problem of poor flame retardancy of existing polyurethane materials, and achieved efficient and long-lasting flame retardant effects and good mechanical properties.

CN119505166APending Publication Date: 2025-02-25LINYI SIKERUI POLYURETHANE MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411824076.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing polyurethane materials have poor flame retardancy and thermal stability, and will depolymerize and release toxic gases during combustion, resulting in the intensification of fire. The existing additive flame retardant modification methods have problems such as large amount of additives, low flame retardant efficiency, and serious mechanical properties damage.

Method used

The phosphorus modified cyclotetrasiloxane is obtained by reacting tetramethyltetravinyl cyclotetrasiloxane with DOPO, and then lignin is reacted with 3-aminopropyldimethoxymethylsilane and phosphorus modified cyclotetrasiloxane in turn to obtain modified lignin microspheres; at the same time, using dioxo monomer and N,N-dimethylhexylamine and other components, isophorone diisocyanate, 1,4-butanediol, etc. are mixed with modified lignin microspheres and deionized water through specific process steps to cure it, and a flame retardant polyurethane composite material is prepared.

Benefits of technology

It realizes excellent flame retardant properties of polyurethane materials, has low usage and high performance effects, can effectively suppress the toxic gases released by combustion, improve the self-repairing and antibacterial properties of the materials, and maintain good mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005183795060000031
    Figure BDA0005183795060000031
  • Figure BDA0005183795060000032
    Figure BDA0005183795060000032
  • Figure BDA0005183795060000041
    Figure BDA0005183795060000041
Patent Text Reader

Abstract

The invention discloses a flame-retardant polyurethane composite material and a preparation process thereof, and relates to the field of high polymer materials. When the flame-retardant polyurethane composite material is prepared, tetramethyl tetravinyl cyclotetrasiloxane reacts with DOPO (9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) to obtain phosphorus modified cyclotetrasiloxane; then, lignin sequentially reacts with 3-aminopropyldimethoxymethylsilane and phosphorus modified cyclotetrasiloxane, and modified lignin microspheres are obtained; the preparation method comprises the following steps: reacting 2, 4-pentanedione, 1, 5-dichloro and hydroxylamine hydrochloride to obtain a dioxime monomer; and uniformly mixing isophorone diisocyanate, 1, 4-butanediol, a dioxime monomer, N, N-dimethyl hexylamine, the modified lignin microspheres and deionized water, pouring into a mold, and curing to obtain the flame-retardant polyurethane composite material. The flame-retardant polyurethane composite material prepared by the preparation method disclosed by the invention has excellent antibacterial property, flame retardance and self-repairing property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, in particular to a flame retardant polyurethane composite material and a preparation process thereof. Background Art

[0002] Polyurethane is an organic high molecular polymer material. Generally, the main chain is an intermediate polymer of medium molecular weight generated by the interaction of oligomer polyols, diisocyanates and catalysts, called prepolymers, which are generally viscous liquids. Further polymerization reaction occurs with diamine or diol chain extenders, and finally converted into high molecular weight polymers. The prepared polymers with repeating structural units of carbamate groups are collectively referred to as such. Polyurethane has good physical and chemical properties, including high elasticity, water resistance, flexibility, heat resistance, excellent mechanical properties and good adhesiveness. Therefore, polyurethane is widely used in various large, medium and small application fields. From flexible foams used in car seats, soft furnishings and other fields, to rigid foams used in thermal insulation and flame retardant materials in walls, home appliances and other fields. In addition, polyurethane is also used in thermoplastic materials used in footwear and medical devices, adhesives and coatings used in automotive interiors and floors, inks on packaging, and fibers in textile materials.

[0003] As a polymer material, polyurethane itself has poor flame retardancy and thermal stability. When it is heated by burning, it will depolymerize and release a large amount of toxic gases and complex small molecules. The small molecules continue to burn and release a large amount of heat to accelerate the cracking of the matrix, forming a positive feedback cycle, so once a fire occurs, it will cause serious consequences. At present, with the increase in the demand for polyurethane products at home and abroad, the performance standard requirements of polyurethane materials have become more stringent. Additive modification is a more commonly used modification method for flame-retardant polyurethane. The preparation process is simple and the cost is low. However, due to the lack of strong covalent connection between the matrix and the flame retardant, there are shortcomings such as large addition amount, low flame retardant efficiency, serious damage to mechanical properties, easy migration, easy moisture absorption, etc., which will cause the flame retardant performance to deteriorate during the combustion process. In contrast, reactive flame retardant modification can give polyurethane permanent flame retardant properties, with the advantages of small introduction amount, high flame retardant efficiency, less influence on mechanical properties and strong flame retardant durability. Therefore, the present invention prepares a polyurethane composite material with excellent flame retardant properties. Summary of the invention

[0004] The purpose of the present invention is to provide a flame retardant polyurethane composite material and a preparation process thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A flame retardant polyurethane composite material is obtained by mixing isophorone diisocyanate, 1,4-butanediol, dioxime monomer, N,N-dimethylhexylamine, modified lignin microspheres and deionized water, pouring the mixture into a mold and curing the mixture.

[0007] As an optimization, the dioxime monomer is obtained by reacting 2,4-pentanedione, 1,5-dichlorobenzene and hydroxylamine hydrochloride.

[0008] As an optimization, the modified lignin microspheres are obtained by reacting lignin with 3-aminopropyldimethoxymethylsilane and phosphorus-modified cyclotetrasiloxane in sequence.

[0009] As an optimization, the lignin model is industrial grade and comes from Pandex (Shanghai) International Trading Co., Ltd.

[0010] As an optimization, the phosphorus-modified cyclotetrasiloxane is obtained by reacting tetramethyltetravinylcyclotetrasiloxane and DOPO.

[0011] A preparation process of a flame retardant polyurethane composite material comprises the following preparation steps:

[0012] (1) Tetramethyltetravinylcyclotetrasiloxane, DOPO, azobisisobutyronitrile and toluene are mixed in a mass ratio of 1:(2-4):(0.04-0.06):(4-6), stirred at 75-85° C. and 100-300 rpm for 9-11 hours, cooled naturally to room temperature, dissolved the lower layer with dichloromethane, added ethyl acetate with a mass of 9-11 times that of dichloromethane after complete dissolution, allowed to stand until the mass of the precipitate remains unchanged, filtered, and dried at 95-105° C. for 7-9 hours to obtain phosphorus-modified cyclotetrasiloxane;

[0013] (2) Lignin, 3-aminopropyldimethoxymethylsilane, a formaldehyde solution with a mass fraction of 36% to 38%, acetic acid, and a 1,4-dioxane aqueous solution with a volume fraction of 75% to 85% were mixed in a mass ratio of 1:

[0014] 1:(0.2-0.4):(0.1-0.3):(1-2):(9.3-9.5) are mixed, stirred at 55-65°C and 100-200rpm for 3-5h, uniformly dripped into deionized water within 1-3h, centrifuged after standing for 1-2h, and dried the precipitate at 45-55°C for 9-11h to obtain pre-modified lignin; pre-modified lignin, phosphorus-modified cyclotetrasiloxane, tetramethylammonium hydroxide silicon alkoxide and toluene are mixed in a mass ratio of 1:(0.4-0.6):(0.01-0.03):(4-6), stirred at 85-95°C and 200-300rpm in a nitrogen atmosphere for 6-8h, naturally cooled to room temperature and filtered, washed with deionized water for 3-5 times, dried at 65-75°C for 8-10h, ground and sieved through 50-70 mesh to obtain modified lignin microspheres;

[0015] (3) 2,4-pentanedione, 1,5-dichlorobenzene, hydroxylamine hydrochloride, sodium acetate and ethanol solution with a mass fraction of 80% to 90% are mixed in a mass ratio of 1: (1.5 to 1.6): (2.3 to 2.5): (70 to 80), refluxed at 85 to 95° C. for 1 to 3 hours, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 3 to 5 times respectively, and dried at 50 to 60° C. for 23 to 25 hours to obtain a dioxime monomer;

[0016] (4) Mix isophorone diisocyanate, 1,4-butanediol, dibutyltin dilaurate and acetone in a mass ratio of 1:(0.2-0.3):(0.01-0.02):(3-4), stir at 45-55°C and 100-200 rpm for 1-3 h, raise the temperature to 55-65°C, add 0.27-0.29 times the mass of isophorone diisocyanate of dioxime monomer, continue stirring for 55-65 min, raise the temperature to 65-75°C, add 0.3 times the mass of isophorone diisocyanate of dioxime monomer, 1 to 0.33 times of N, N-dimethylhexylamine, continue stirring for 7 to 9 hours, add 0.5 to 0.6 times the mass of isophorone diisocyanate modified lignin microsphere solution, continue stirring, add 1 to 2 times the mass of isophorone diisocyanate deionized water, disperse at 11000 to 13000 rpm for 25 to 35 minutes, rotary evaporate at 45 to 55 ° C for 20 to 30 minutes, pour into a mold, volatilize at 55 to 65 ° C for 1 to 3 hours, and stand at room temperature for 24 hours to obtain a flame retardant polyurethane composite material.

[0017] As an optimization, the reaction equation of the phosphorus-modified cyclotetrasiloxane in step (1) is:

[0018]

[0019] As an optimization, the reaction equation of the pre-modified lignin in step (2) is:

[0020]

[0021] As an optimization, the reaction equation of the modified lignin microspheres in step (2) is:

[0022]

[0023] As an optimization, the reaction equation of the dioxime monomer in step (3) is:

[0024]

[0025] As an optimization, the modified lignin microsphere solution in step (4) is obtained by mixing the modified lignin microspheres and N,N-dimethylformamide in a mass ratio of 1:14.

[0026] As an optimization, the reaction equation of the flame-retardant polyurethane composite material in step (4) is:

[0027]

[0028] Where R1 is: R2 is: R3 is:

[0029]

[0030] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0031] When preparing the flame-retardant polyurethane composite material, the present invention comprises the following steps: reacting tetramethyltetravinylcyclotetrasiloxane with DOPO to obtain phosphorus-modified cyclotetrasiloxane; reacting lignin with 3-aminopropyldimethoxymethylsilane and phosphorus-modified cyclotetrasiloxane in sequence to obtain modified lignin microspheres; reacting 2,4-pentanedione, 1,5-dichlorobenzene and hydroxylamine hydrochloride to obtain a dioxime monomer; and mixing isophorone diisocyanate, 1,4-butanediol, a dioxime monomer, N,N-dimethylhexylamine, the modified lignin microspheres and deionized water, and then pouring the mixture into a mold for curing to obtain the flame-retardant polyurethane composite material.

[0032] First, tetramethyltetravinylcyclotetrasiloxane and DOPO are reacted to obtain phosphorus-modified cyclotetrasiloxane; then, lignin is reacted with 3-aminopropyldimethoxymethylsilane and phosphorus-modified cyclotetrasiloxane in sequence to obtain modified lignin microspheres; phosphorus-containing compounds decompose at high temperatures to generate volatile small molecular phosphides and phosphorus-containing free radicals, which capture free radicals in the flame area and inhibit the chain branching step to perform gas phase flame retardancy; polysiloxane will precipitate onto the surface of the matrix at high temperatures, and the polysiloxane enriched on the surface during combustion The oxane substance will decompose to form a glassy and dense protective layer for condensed phase flame retardancy; phosphorus-modified cyclotetrasiloxane is obtained by phosphorus-hydrogen addition, and phosphorus and silicon are chemically bonded for synergistic flame retardancy, achieving a low-dosage and high-performance effect; 3-aminopropyldimethoxymethylsilane is grafted onto lignin via the Mannich reaction, and siloxane reaction sites are introduced at the ortho position of the phenolic hydroxyl group of lignin, and phosphorus-modified cyclotetrasiloxane is further grafted to form lignin microspheres connected by silicon-oxygen chains, thereby improving the flame retardant properties of flame-retardant polyurethane composites.

[0033] Secondly, 2,4-pentanedione, 1,5-dichlorobenzene and hydroxylamine hydrochloride are reacted to obtain a dioxime monomer; then isophorone diisocyanate, 1,4-butanediol, dioxime monomer, N,N-dimethylhexylamine, modified lignin microspheres and deionized water are mixed and poured into a mold for curing to obtain a flame-retardant polyurethane composite material; the oxime hydroxyl group and the isocyanate bond can form a dynamic oxime-carbamate bond with excellent reversibility, and a dioxime monomer with an oxime hydroxyl group and a chlorine atom is formed by the reaction of 2,4-pentanedione, 1,5-dichlorobenzene and hydroxylamine hydrochloride, which participates in the polymerization of the polyurethane main chain and improves the self-healing performance of the flame-retardant polyurethane composite material; at the same time, the chlorine atom in the dioxime monomer reacts with N,N-dimethylhexylamine to form a cationic quaternary ammonium salt, which can destroy the negatively charged bacterial cell membrane, inhibit cell metabolism, and improve the antibacterial performance of the flame-retardant polyurethane composite material. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0035] Embodiment 1:

[0036] A preparation process of a flame retardant polyurethane composite material, the preparation process of the flame retardant polyurethane composite material comprising the following preparation steps:

[0037] (1) Tetramethyltetravinylcyclotetrasiloxane, DOPO, azobisisobutyronitrile and toluene were mixed in a mass ratio of 1:2:0.04:4, stirred at 75°C and 100 rpm for 11 hours, cooled naturally to room temperature, dissolved the lower layer with dichloromethane, added ethyl acetate 9 times the mass of dichloromethane after complete dissolution, allowed to stand until the mass of the precipitate remained unchanged, filtered, and dried at 95°C for 9 hours to obtain phosphorus-modified cyclotetrasiloxane;

[0038] (2) Mix lignin, 3-aminopropyldimethoxymethylsilane, 36% formaldehyde solution, acetic acid, and 75% 1,4-dioxane aqueous solution in a mass ratio of 1:0.2:0.1:1:9.3, stir at 55°C and 100 rpm for 5 h, drip into deionized water at a uniform rate within 1 h, let stand for 1 h and then centrifuge, and dry the precipitate at 45°C for 11 h to obtain pre-modified lignin; mix pre-modified lignin, phosphorus-modified cyclotetrasiloxane, tetramethylammonium hydroxide silicon alkoxide and toluene in a mass ratio of 1:0.4:0.01:4, stir at 85°C and 200 rpm for 8 h in a nitrogen atmosphere, filter after naturally cooling to room temperature, wash with deionized water 3 times, dry at 65°C for 10 h, grind and sieve 50 mesh to obtain modified lignin microspheres;

[0039] (3) 2,4-pentanedione, 1,5-dichlorobenzene, hydroxylamine hydrochloride, sodium acetate and 80% ethanol solution were mixed in a mass ratio of 1:1.5:2.3:70, refluxed at 85°C for 3 hours, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 3 times respectively, and dried at 50°C for 25 hours to obtain a dioxime monomer;

[0040] (4) Mix isophorone diisocyanate, 1,4-butanediol, dibutyltin dilaurate and acetone in a mass ratio of 1:0.2:0.01:3, stir at 45°C and 100 rpm for 3 h, heat to 55°C, add dioxime monomer in an amount of 0.27 times the mass of isophorone diisocyanate, continue stirring for 65 min, heat to 65°C, add N,N-dimethylhexylamine in an amount of 0.31 times the mass of isophorone diisocyanate, continue stirring for 9 h, add modified lignin microsphere solution in an amount of 0.5 times the mass of isophorone diisocyanate, continue stirring, add deionized water in an amount of 1 times the mass of isophorone diisocyanate, disperse at 11000 rpm for 35 min, rotary evaporate at 45°C for 30 min, pour into a mold, evaporate at 55°C for 3 h, and let stand at room temperature for 23 h to obtain a flame-retardant polyurethane composite material.

[0041] Embodiment 2:

[0042] A preparation process of a flame retardant polyurethane composite material, the preparation process of the flame retardant polyurethane composite material comprising the following preparation steps:

[0043] (1) Tetramethyltetravinylcyclotetrasiloxane, DOPO, azobisisobutyronitrile and toluene were mixed in a mass ratio of 1:3:0.05:5, stirred at 80°C and 200 rpm for 10 h, cooled naturally to room temperature, dissolved the lower layer with dichloromethane, added ethyl acetate 10 times the mass of dichloromethane after complete dissolution, allowed to stand until the mass of the precipitate remained unchanged, filtered, and dried at 100°C for 8 h to obtain phosphorus-modified cyclotetrasiloxane;

[0044] (2) Mix lignin, 3-aminopropyldimethoxymethylsilane, 37% formaldehyde solution, acetic acid, and 80% 1,4-dioxane aqueous solution in a mass ratio of 1:0.3:0.2:1.5:9.4, stir at 60°C and 150 rpm for 4 h, drip into deionized water at a uniform rate within 2 h, let stand for 1.5 h and then centrifuge, and dry the precipitate at 50°C for 10 h to obtain pre-modified lignin; mix pre-modified lignin, phosphorus-modified cyclotetrasiloxane, tetramethylammonium hydroxide silicon alkoxide and toluene in a mass ratio of 1:0.5:0.02:5, stir at 90°C and 250 rpm for 7 h in a nitrogen atmosphere, filter after naturally cooling to room temperature, wash with deionized water 4 times, dry at 70°C for 9 h, grind and sieve 60 mesh to obtain modified lignin microspheres;

[0045] (3) 2,4-pentanedione, 1,5-dichlorobenzene, hydroxylamine hydrochloride, sodium acetate and 85% ethanol solution were mixed in a mass ratio of 1:1.55:2.4:75, refluxed at 90°C for 2 hours, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 4 times respectively, and dried at 55°C for 24 hours to obtain a dioxime monomer;

[0046] (4) Mix isophorone diisocyanate, 1,4-butanediol, dibutyltin dilaurate and acetone in a mass ratio of 1:0.25:0.015:3.5, stir at 50°C and 150 rpm for 2 h, heat to 60°C, add dioxime monomer in an amount of 0.28 times the mass of isophorone diisocyanate, continue stirring for 60 min, heat to 70°C, add N,N-dimethylhexylamine in an amount of 0.32 times the mass of isophorone diisocyanate, continue stirring for 8 h, add modified lignin microsphere solution in an amount of 0.55 times the mass of isophorone diisocyanate, continue stirring, add deionized water in an amount of 1.5 times the mass of isophorone diisocyanate, disperse at 12000 rpm for 30 min, rotary evaporate at 50°C for 25 min, pour into a mold, evaporate at 60°C for 2 h, and let stand at room temperature for 24 h to obtain a flame retardant polyurethane composite material.

[0047] Embodiment 3:

[0048] A preparation process of a flame retardant polyurethane composite material, the preparation process of the flame retardant polyurethane composite material comprising the following preparation steps:

[0049] (1) Tetramethyltetravinylcyclotetrasiloxane, DOPO, azobisisobutyronitrile and toluene were mixed in a mass ratio of 1:4:0.06:6, stirred at 85°C and 300 rpm for 9 hours, cooled naturally to room temperature, dissolved the lower layer with dichloromethane, added ethyl acetate 11 times the mass of dichloromethane after complete dissolution, allowed to stand until the mass of the precipitate remained unchanged, filtered, and dried at 105°C for 7 hours to obtain phosphorus-modified cyclotetrasiloxane;

[0050] (2) Mix lignin, 3-aminopropyldimethoxymethylsilane, 38% formaldehyde solution, acetic acid, and 85% 1,4-dioxane aqueous solution in a mass ratio of 1:0.4:0.3:2:9.5, stir at 65°C and 200 rpm for 3 h, drip into deionized water at a uniform rate within 3 h, let stand for 2 h and then centrifuge, and dry the precipitate at 55°C for 9 h to obtain pre-modified lignin; mix pre-modified lignin, phosphorus-modified cyclotetrasiloxane, tetramethylammonium hydroxide silicon alkoxide and toluene in a mass ratio of 1:0.6:0.03:6, stir at 95°C and 300 rpm for 6 h in a nitrogen atmosphere, filter after naturally cooling to room temperature, wash with deionized water 5 times, dry at 75°C for 8 h, grind and sieve 70 mesh to obtain modified lignin microspheres;

[0051] (3) 2,4-pentanedione, 1,5-dichlorobenzene, hydroxylamine hydrochloride, sodium acetate and 90% ethanol solution were mixed in a mass ratio of 1:1.6:2.5:80, refluxed at 95°C for 1 hour, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 5 times respectively, and dried at 60°C for 23 hours to obtain a dioxime monomer;

[0052] (4) Mix isophorone diisocyanate, 1,4-butanediol, dibutyltin dilaurate and acetone in a mass ratio of 1:0.3:0.02:4, stir at 55°C and 200 rpm for 1 h, heat to 65°C, add dioxime monomer in an amount of 0.29 times the mass of isophorone diisocyanate, continue stirring for 55 min, heat to 75°C, add N,N-dimethylhexylamine in an amount of 0.33 times the mass of isophorone diisocyanate, continue stirring for 7 h, add modified lignin microsphere solution in an amount of 0.6 times the mass of isophorone diisocyanate, continue stirring, add deionized water in an amount of 2 times the mass of isophorone diisocyanate, disperse at 13000 rpm for 25 min, rotary evaporate at 55°C for 20 min, pour into a mold, evaporate at 65°C for 1 h, and let stand at room temperature for 25 h to obtain a flame-retardant polyurethane composite material.

[0053] Comparative Example 1:

[0054] A preparation process of a flame retardant polyurethane composite material, the preparation process of the flame retardant polyurethane composite material comprising the following preparation steps:

[0055] (1) lignin, 3-aminopropyldimethoxymethylsilane, a 37% formaldehyde solution, acetic acid, and an 80% 1,4-dioxane aqueous solution were mixed in a mass ratio of 1:0.3:0.2:1.5:9.4, stirred at 60°C and 150 rpm for 4 hours, and uniformly added into deionized water within 2 hours. After standing for 1.5 hours, the mixture was centrifuged and the precipitate was dried at 50°C for 10 hours to obtain pre-modified lignin;

[0056] (3) 2,4-pentanedione, 1,5-dichlorobenzene, hydroxylamine hydrochloride, sodium acetate and 85% ethanol solution were mixed in a mass ratio of 1:1.55:2.4:75, refluxed at 90°C for 2 hours, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 4 times respectively, and dried at 55°C for 24 hours to obtain a dioxime monomer;

[0057] (4) Mix isophorone diisocyanate, 1,4-butanediol, dibutyltin dilaurate and acetone in a mass ratio of 1:0.25:0.015:3.5, stir at 50°C and 150rpm for 2h, heat to 60°C, add dioxime monomer in an amount of 0.28 times the mass of isophorone diisocyanate, continue stirring for 60min, heat to 70°C, add N,N-dimethylhexylamine in an amount of 0.32 times the mass of isophorone diisocyanate, continue stirring for 8h, add pre-modified lignin solution in an amount of 0.55 times the mass of isophorone diisocyanate, continue stirring, add deionized water in an amount of 1.5 times the mass of isophorone diisocyanate, disperse at 12000rpm for 30min, rotary evaporate at 50°C for 25min, pour into a mold, evaporate at 60°C for 2h, and let stand at room temperature for 24h to obtain a flame-retardant polyurethane composite material.

[0058] The pre-modified lignin solution is obtained by mixing the pre-modified lignin and N,N-dimethylformamide in a mass ratio of 1:14.

[0059] Comparative Example 2:

[0060] A preparation process of a flame retardant polyurethane composite material, the preparation process of the flame retardant polyurethane composite material comprising the following preparation steps:

[0061] (1) Tetramethyltetravinylcyclotetrasiloxane, DOPO, azobisisobutyronitrile and toluene were mixed in a mass ratio of 1:3:0.05:5, stirred at 80°C and 200 rpm for 10 h, cooled naturally to room temperature, dissolved the lower layer with dichloromethane, added ethyl acetate 10 times the mass of dichloromethane after complete dissolution, allowed to stand until the mass of the precipitate remained unchanged, filtered, and dried at 100°C for 8 h to obtain phosphorus-modified cyclotetrasiloxane;

[0062] (2) Mix lignin, 3-aminopropyldimethoxymethylsilane, 37% formaldehyde solution, acetic acid, and 80% 1,4-dioxane aqueous solution in a mass ratio of 1:0.3:0.2:1.5:9.4, stir at 60°C and 150 rpm for 4 h, drip into deionized water at a uniform rate within 2 h, let stand for 1.5 h and then centrifuge, and dry the precipitate at 50°C for 10 h to obtain pre-modified lignin; mix pre-modified lignin, phosphorus-modified cyclotetrasiloxane, tetramethylammonium hydroxide silicon alkoxide and toluene in a mass ratio of 1:0.5:0.02:5, stir at 90°C and 250 rpm for 7 h in a nitrogen atmosphere, filter after naturally cooling to room temperature, wash with deionized water 4 times, dry at 70°C for 9 h, grind and sieve 60 mesh to obtain modified lignin microspheres;

[0063] (3) 2,4-pentanedione, 1,5-dichlorobenzene, hydroxylamine hydrochloride, sodium acetate and 85% ethanol solution were mixed in a mass ratio of 1:1.55:2.4:75, refluxed at 90°C for 2 hours, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 4 times respectively, and dried at 55°C for 24 hours to obtain a dioxime monomer;

[0064] (4) Mix isophorone diisocyanate, 1,4-butanediol, dibutyltin dilaurate and acetone in a mass ratio of 1:0.25:0.015:3.5, stir at 50°C and 150 rpm for 2 h, raise the temperature to 60°C, add 0.28 times the mass of isophorone diisocyanate dioxime monomer, continue stirring for 60 min, add 0.55 times the mass of isophorone diisocyanate modified lignin microsphere solution, continue stirring, add 1.5 times the mass of isophorone diisocyanate deionized water, disperse at 12000 rpm for 30 min, rotary evaporate at 50°C for 25 min, pour into a mold, evaporate at 60°C for 2 h, and let stand at room temperature for 24 h to obtain a flame retardant polyurethane composite material.

[0065] Comparative Example 3:

[0066] A preparation process of a flame retardant polyurethane composite material, the preparation process of the flame retardant polyurethane composite material comprising the following preparation steps:

[0067] (1) Tetramethyltetravinylcyclotetrasiloxane, DOPO, azobisisobutyronitrile and toluene were mixed in a mass ratio of 1:3:0.05:5, stirred at 80°C and 200 rpm for 10 h, cooled naturally to room temperature, dissolved the lower layer with dichloromethane, added ethyl acetate 10 times the mass of dichloromethane after complete dissolution, allowed to stand until the mass of the precipitate remained unchanged, filtered, and dried at 100°C for 8 h to obtain phosphorus-modified cyclotetrasiloxane;

[0068] (2) Mix lignin, 3-aminopropyldimethoxymethylsilane, 37% formaldehyde solution, acetic acid, and 80% 1,4-dioxane aqueous solution in a mass ratio of 1:0.3:0.2:1.5:9.4, stir at 60°C and 150 rpm for 4 h, drip into deionized water at a uniform rate within 2 h, let stand for 1.5 h and then centrifuge, and dry the precipitate at 50°C for 10 h to obtain pre-modified lignin; mix pre-modified lignin, phosphorus-modified cyclotetrasiloxane, tetramethylammonium hydroxide silicon alkoxide and toluene in a mass ratio of 1:0.5:0.02:5, stir at 90°C and 250 rpm for 7 h in a nitrogen atmosphere, filter after naturally cooling to room temperature, wash with deionized water 4 times, dry at 70°C for 9 h, grind and sieve 60 mesh to obtain modified lignin microspheres;

[0069] (3) Mix isophorone diisocyanate, 1,4-butanediol, dibutyltin dilaurate and acetone in a mass ratio of 1:0.25:0.015:3.5, stir at 50°C and 150 rpm for 2 h, raise the temperature to 60°C, add a modified lignin microsphere solution with a mass of 0.55 times that of isophorone diisocyanate, continue stirring, add deionized water with a mass of 1.5 times that of isophorone diisocyanate, disperse at 12000 rpm for 30 min, rotary evaporate at 50°C for 25 min, pour into a mold, evaporate at 60°C for 2 h, and let stand at room temperature for 24 h to obtain a flame retardant polyurethane composite material.

[0070] Test Case

[0071] 1. Flame retardancy

[0072] Test method: The flame-retardant polyurethane composite materials obtained in each example and the comparative example were made into samples according to GB / T-2406, and the limiting oxygen index was tested using the M606B limiting oxygen index instrument produced by Qingdao Shanfang.

[0073] 2. Antibacterial

[0074] Test method: Take circular samples with a diameter of 1 cm from the flame-retardant polyurethane composite materials obtained in each embodiment and the comparative example according to GB / T31402, evenly spread 40 μl of activated Escherichia coli on the solid agar medium, place the sample on the medium, and culture it at a constant temperature of 37°C for 24 hours, and record the width of the inhibition zone around the sample.

[0075] 3. Self-healing

[0076] Test method: The flame-retardant polyurethane composite materials obtained in each embodiment and the comparative example were cut into standard dumbbell-shaped samples of 2mm×10mm according to GB / T8949, and the tensile strength σ0 was tested under the conditions of 25°C, 75% relative humidity, and 20mm / min; the sample was cut in the middle and the cross sections were tightly contacted, and it was allowed to stand at 80°C for 24h, the tensile strength σ1 was measured, and the repair rate = σ1 / σ0*100% was calculated.

[0077] Table 1 below shows the analysis results of the antibacterial property, flame retardancy and self-healing property of the flame-retardant polyurethane composite materials of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.

[0078] Table 1

[0079]

[0080]

[0081] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the flame-retardant polyurethane composite material prepared in the present invention has good antibacterial properties, flame retardancy and self-repairing properties.

[0082] By comparison, the limiting oxygen index of Examples 1, 2, and 3 is higher than that of Comparative Example 1, which indicates that the phosphorus-containing compound decomposes at high temperature to generate volatile small molecular phosphides and phosphorus-containing free radicals, capture free radicals in the flame area, and inhibit the chain branching step to perform gas phase flame retardancy; polysiloxane will precipitate onto the surface of the substrate at high temperature, and the polysiloxane material enriched on the surface will decompose during combustion to form a glass-like dense protective layer for condensed phase flame retardancy; phosphorus-modified cyclotetrasiloxane is obtained by phosphorus-hydrogen addition, and phosphorus and silicon are chemically bonded to achieve synergistic flame retardancy, achieving a low dosage and high performance effect; 3-aminopropyldimethoxymethylsilane is grafted onto lignin by the Mannich reaction, and a siloxane reaction site is introduced at the ortho position of the phenolic hydroxyl group of lignin, and phosphorus-modified cyclotetrasiloxane is further grafted to form lignin microspheres connected by silicon-oxygen chains, thereby improving the flame retardant properties of the flame-retardant polyurethane composite material.

[0083] By comparison, the width of the inhibition zone of Examples 1, 2, and 3 is larger than that of Comparative Example 2, indicating that the chlorine atoms in the dioxime monomer react with N,N-dimethylhexylamine to form a cationic quaternary ammonium salt, which can destroy the negatively charged bacterial cell membrane, inhibit cell metabolism, and improve the antibacterial properties of the flame-retardant polyurethane composite material.

[0084] By comparison, the antibacterial zone widths of Examples 1, 2, and 3 are larger than those of Comparative Example 3 and the repair rates are higher, indicating that the bonding of oxime hydroxyl groups and isocyanate can form dynamic oxime-carbamate bonds with excellent reversibility. Dioxime monomers with oxime hydroxyl groups and chlorine atoms are formed by the reaction of 2,4-pentanedione, 1,5-dichlorobenzene and hydroxylamine hydrochloride, and participate in the polymerization of the polyurethane main chain, thereby improving the self-healing properties of the flame-retardant polyurethane composite material.

[0085] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A flame retardant polyurethane composite material, characterized in that: The flame-retardant polyurethane composite material is prepared by mixing isophorone diisocyanate, 1,4-butanediol, dioxime monomer, N,N-dimethylhexylamine, modified lignin microspheres and deionized water, and then pouring the mixture into a mold for curing. The dioxime monomer is obtained by reacting 2,4-pentanedione, 1,5-dichlorobenzene and hydroxylamine hydrochloride; The modified lignin microspheres are obtained by sequentially reacting lignin with 3-aminopropyldimethoxymethylsilane and phosphorus-modified cyclotetrasiloxane; The phosphorus-modified cyclotetrasiloxane is obtained by reacting tetramethyltetravinylcyclotetrasiloxane and DOPO.

2. A process for preparing a flame retardant polyurethane composite material, characterized in that: The method comprises the following preparation steps: (1) Tetramethyltetravinylcyclotetrasiloxane, DOPO, azobisisobutyronitrile and toluene are mixed in a mass ratio of 1:(2-4):(0.04-0.06):(4-6), stirred at 75-85° C. and 100-300 rpm for 9-11 hours, cooled naturally to room temperature, dissolved the lower layer with dichloromethane, added ethyl acetate with a mass of 9-11 times that of dichloromethane after complete dissolution, allowed to stand until the mass of the precipitate remains unchanged, filtered, and dried at 95-105° C. for 7-9 hours to obtain phosphorus-modified cyclotetrasiloxane; (2) Mix lignin, 3-aminopropyldimethoxymethylsilane, a formaldehyde solution with a mass fraction of 36% to 38%, acetic acid, and a 1,4-dioxane aqueous solution with a volume fraction of 75% to 85% in a mass ratio of 1: (0.2 to 0.4): (0.1 to 0.3): (1 to 2): (9.3 to 9.5), stir at 55 to 65° C. and 100 to 200 rpm for 3 to 5 h, drip into deionized water at a uniform speed within 1 to 3 h, let stand for 1 to 2 h, and then centrifuge. The precipitate is heated at 45 to 55° C. Drying for 9 to 11 hours to obtain pre-modified lignin; mixing the pre-modified lignin, phosphorus-modified cyclotetrasiloxane, tetramethylammonium hydroxide silicon alkoxide and toluene in a mass ratio of 1: (0.4 to 0.6): (0.01 to 0.03): (4 to 6), stirring for 6 to 8 hours at 85 to 95° C. and 200 to 300 rpm in a nitrogen atmosphere, naturally cooling to room temperature and filtering, washing with deionized water for 3 to 5 times, drying at 65 to 75° C. for 8 to 10 hours, grinding and sieving through 50 to 70 meshes to obtain modified lignin microspheres; (3) 2,4-pentanedione, 1,5-dichlorobenzene, hydroxylamine hydrochloride, sodium acetate and ethanol solution with a mass fraction of 80% to 90% are mixed in a mass ratio of 1: (1.5 to 1.6): (2.3 to 2.5): (70 to 80), refluxed at 85 to 95° C. for 1 to 3 hours, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 3 to 5 times respectively, and dried at 50 to 60° C. for 23 to 25 hours to obtain a dioxime monomer; (4) Mix isophorone diisocyanate, 1,4-butanediol, dibutyltin dilaurate and acetone in a mass ratio of 1:(0.2-0.3):(0.01-0.02):(3-4), stir at 45-55°C and 100-200 rpm for 1-3 h, raise the temperature to 55-65°C, add 0.27-0.29 times the mass of isophorone diisocyanate of dioxime monomer, continue stirring for 55-65 min, raise the temperature to 65-75°C, add 0.3 times the mass of isophorone diisocyanate of dioxime monomer, 1 to 0.33 times of N, N-dimethylhexylamine, continue stirring for 7 to 9 hours, add 0.5 to 0.6 times the mass of isophorone diisocyanate modified lignin microsphere solution, continue stirring, add 1 to 2 times the mass of isophorone diisocyanate deionized water, disperse at 11000 to 13000 rpm for 25 to 35 minutes, rotary evaporate at 45 to 55 ° C for 20 to 30 minutes, pour into a mold, volatilize at 55 to 65 ° C for 1 to 3 hours, and stand at room temperature for 24 hours to obtain a flame retardant polyurethane composite material.

3. The process for preparing a flame-retardant polyurethane composite material according to claim 2, characterized in that: The reaction equation of the phosphorus-modified cyclotetrasiloxane in step (1) is:

4. The process for preparing a flame-retardant polyurethane composite material according to claim 2, characterized in that: The reaction equation of the pre-modified lignin in step (2) is:

5. The process for preparing a flame-retardant polyurethane composite material according to claim 2, characterized in that: The reaction equation of the modified lignin microspheres in step (2) is:

6. The process for preparing a flame-retardant polyurethane composite material according to claim 2, characterized in that: The reaction equation of the dioxime monomer in step (3) is:

7. The process for preparing a flame-retardant polyurethane composite material according to claim 2, characterized in that: The modified lignin microsphere solution in step (4) is obtained by mixing modified lignin microspheres and N,N-dimethylformamide in a mass ratio of 1:

14.

8. The process for preparing a flame-retardant polyurethane composite material according to claim 2, characterized in that: The reaction equation of the flame retardant polyurethane composite material in step (4) is: Where R1 is: R2 is: R3 is:

Citation Information

Cited By

  • Rigid polyurethane foam based on composite flame-retardant coating as well as preparation method and application of rigid polyurethane foam

    CN121271019A